Study on music visualisation - Tjhoea, Doddy Anderson (2018)
The aim of this project is to study static music visualisation techniques. Currently available music visualisation technologies, applications, and literature were reviewed in order to identify a research gap. A static music visualisation tool was designed and implemented to fill that niche. This tool took the form of an audio player program that displayed a visual to provide both information and aesthetic pleasure, catering to both the professional and public audience. A user study was done to verify the effectiveness of this tool. It was concluded that this static music visualisation approach was effective and had potential in further applications in visualisation.